Cracking and flexural behaviors on cement treated crushed rock for thin flexible pavement - Siripun, K.; Jitsangiam, Peerapong; Nikraz, Hamid; Leek, C. (2012)
Fatigue cracking is considered to be one of the most important types of distress affecting the performance of flexible pavements on major highways. This report analyses the results of a laboratory study of the static and fatigue response of a typical Western Australia Cement Treated Base (CTB) to evaluates its mechanical parameters i.e. flexural strength, flexural stiffness and tensile strains. Five different series of cement content were evaluated in the mix of 1%, 2%, 3%, 4% and 5%. Two major types of testing were conducted for the purpose of this study, i.e. Flexural Fatigue Tests (dynamic loading) and Flexural Beam Tests (static loading). The flexural fatigue tests were carried out with strain control mode. From the tests, the flexural stiffness for each specimen was calculated. The flexural stiffness was obtained from maximum tensile strains on the bottom of the specimens. The outcomes of the paper are as summarized as follow: First, 1% to 3% CTB was found out to be classified as modified material while 4% and 5% CTB are categorized as stabilized materials. Second, fatigue cracking phenomenon can be seen in stabilized materials (4% and 5% CTB) while other types of distress may affect the behavior of modified materials (1 to 3% CTB). Third, 4% cemented material is observed to be the most suitable material to perform under fatigue loading conditions. Fourth, a series of recommendations are presented for further research i.e. the Flexural Fatigue Test be conducted at a suitable (lower) strain value instead of the 400 µe magnitude used in this research. © 2012 Taylor & Francis Group.